2016
DOI: 10.3892/ol.2016.5283
|View full text |Cite
|
Sign up to set email alerts
|

N-terminal truncated carboxypeptidase E expression is associated with poor prognosis of lung adenocarcinoma

Abstract: Abstract. Lung cancer is a malignant tumor with high morbidity and mortality rates. To date, no suitable molecular diagnostic tool to predict disease recurrence and metastasis has been identified. The current study aimed to evaluate the potential of N-terminal truncated carboxypeptidase E (CPEΔN) to predict the recurrence and metastasis of lung adenocarcinoma. Western blotting revealed the co-expression of CPE and CPEΔN in the surgically collected pathological and pericarcinoma tissues tissues of 62.1% (59/95)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Multivariate Cox regression analysis revealed that CPE-∆N expression was associated with lymph node and distant metastasis. Patients having CPE-∆N expression exhibited higher 3-year postoperative recurrence and metastasis rates than patients lacking CPE-∆N expression [20]. Enhanced CPE expression was documented in colorectal cancer (CRC) cell lines and patient tumor samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multivariate Cox regression analysis revealed that CPE-∆N expression was associated with lymph node and distant metastasis. Patients having CPE-∆N expression exhibited higher 3-year postoperative recurrence and metastasis rates than patients lacking CPE-∆N expression [20]. Enhanced CPE expression was documented in colorectal cancer (CRC) cell lines and patient tumor samples.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of the 40 kDa CPE-ΔN in HCC cells upregulated the expression of metastasis-related genes, including chemokine receptor CXCR2, which is associated with PC malignancy [16,17,18,19]. Elevated tumor expression of CPE-ΔN protein has been correlated with poor prognosis in lung adenocarcinoma patients [20]. Additionally, overexpression of a 46 kDa CPE-ΔN isoform in osteosarcoma (OS) cells resulted in enhanced cell growth, migration, and invasion [21].…”
Section: Introductionmentioning
confidence: 99%
“…This CPE-ΔN variant acts in the nucleus to promote mouse embryonic cortical neuronal survival through up-regulation of expression of many genes that promote proliferation, differentiation, axonal guidance and cell migration, as well as programmed cell death, all events that take place during the formation of the nervous system [22]. Similarly, CPE has been found in the nucleus as revealed by immunohistochemical (IHC) staining in some human cancers [21, 23]. Despite previous studies implicating the CPE variant induces proliferation and invasion in various tumor cell lines and to promote growth and metastasis of tumors in orthotopic models of nude mice, and could potentially be a biomarker in predicting metastasis and recurrence of cancer [13, 16, 23], the complete characterization of this CPE variant has not yet been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, CPE has been found in the nucleus as revealed by immunohistochemical (IHC) staining in some human cancers [21, 23]. Despite previous studies implicating the CPE variant induces proliferation and invasion in various tumor cell lines and to promote growth and metastasis of tumors in orthotopic models of nude mice, and could potentially be a biomarker in predicting metastasis and recurrence of cancer [13, 16, 23], the complete characterization of this CPE variant has not yet been carried out. In order to better understand the structure, regulation and biological function of this CPE-ΔN variant, we have now undertaken to clone and characterize the mRNA.…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer is a kind of malignant tumor with extremely high morbidity and mortality, which poses a great threat to human health and life . According to statistics, the 5‐year survival rate of patients with lung cancer has not improved significantly over the years .…”
Section: Introductionmentioning
confidence: 99%